Nontraumatic hemoabdomen and pancytopenia secondary to myelolipoma in a cat. Issue 2 (12th November 2021) - Haak, Carol E.; Zumbo, Brittany; Allen, Julie; Kunz, Brittany
Abstract: Objective: (1) To report an unusual etiology for nontraumatic hemoabdomen in cats, and (2) to describe onset and recovery from severe, unexpected pancytopenia seen after surgical removal of a large intra‐abdominal myelolipoma. Case Summary: A 14‐year‐old neutered male domestic shorthair cat was presented for emergent treatment of suspected nontraumatic hemoabdomen. A hyperechoic mass, with ultrasonographic echogenicity similar to fat, was found in the right cranial abdomen and believed to be associated with the mesentery. Cytological examination of abdominal fluid identified marked extramedullary hematopoiesis within the hemorrhagic effusion. Exploratory laparotomy identified a hepatic mass, which was resected, and revealed to be a hepatic myelolipoma on histopathological examination. The patient's initial recovery was uneventful. However, continued hyporexia resulted in readmission 4 days postoperatively, at which time the patient was found to have a profound, tri‐lineage pancytopenia, and cytological evidence indicative of bone marrow recovery. The pancytopenia resolved with continued medical management and supportive care. New or Unique Information Provided: Ruptured myelolipoma is not a commonly considered differential for nontraumatic hemoabdomen in cats. Furthermore, severe pancytopenia is unexpected following surgical resection of a myelolipoma. This case provides a unique clinical presentation of both nontraumatic hemoabdomen and bone marrow recovery.